LC-MS/MS method for the simultaneous estimation of Cefepime and Tazobactam in dog plasma - Patil, Kiran R.; Naik, Sukanta K.; Zope, Vineet S.; Chavan, Rajesh P.; Yeole, Ravindra D. (Drug Analytical Research, 2026)
A high performance liquid chromatography (HPLC) method with tandem mass spectrometric detection (MS/MS) has been developed and validated for the simultaneous quantification of cefepime and tazobactam in dog plasma. The method was developed on amide column with isocratic elution. The developed method is simple and economic in terms of sample preparation. The method is specific, sensitive, accurate, precise and robust. The method was successfully applied for pre-clinical pharmaco-kinetic studies in dogs. The Tmax was found to be 0.5 hr, the mean Cmax and AUC(0-12) displayed dose proportionate response.